One-Put Ferula-Mediated Synthesis of Biogenic Silver Nanoparticles with More Antimicrobial Effect and Promising Human Cell Biocompatibility. (15th September 2022) - Gholami, Ahmad; Mousavi, Seyyed Mojtaba; Shomali, Ali; Hashemi, Seyyed Alireza; Abootalebi, Seyedeh Narjes; Chiang, Wei-Hung; Barzegar, Alireza; Shokripoor, Mansooreh; Zadeh, Abdolali Mohaghegh
Abstract : The biogenic synthesis of silver nanoparticles has recently attracted more attention to counter microbial resistance, which has been one of the medical concerns in the last decade. This research expresses the biogenic synthesis of silver nanoparticles utilizing Ferula assafoetida aqueous extract (Fer@AgNP) as a reducing and capping agent. The total parts of the plant were extracted from an aqueous solution (FerEX) and characterized using GC/MS apparatus. The Fer@AgNP and chemically synthesized silver nanoparticles (AgNPs) were characterized using UV-vis, Fourier transform infrared (FTIR) spectroscopies, field emission-scanning transmission electron microscopy, powder X-ray diffraction analysis, and energy-dispersive X-ray spectroscopy. The impacts of nanoparticles and FerEX were evaluated against four pathogenic bacterial strains, including Staphylococcus aureus, Escherichia coli, Salmonella typhi, and Enterococcus faecalis, using the microdilution method. The biocompatibility of compounds was also evaluated on human cell line L-929 using MTT and human blood cells using the hemolytic assay. The major compounds found in FerEX were sulfur-containing compounds such as butyl disulfides (45.36%) and monoterpenes such as α -pinene (25.66%), β -pinene (16.31%), and ocimene (7.26%). The characterizations of materials confirmed the hexagonal structure of AgNPs. The sizes of cAgNP and Fer@AgNP were about 42.7 nm and 22.5 nm. The antimicrobial activity of Fer@AgNP was considerably developed and reached MIC values ranging from 10 to 50  μ g/mL compared to AgNP, which showed MIC values ranging from 50 to 100  μ g/mL. The biocompatibility assessment showed that the Fer@AgNP was improved compared to AgNP and had a minimal toxic impact on the normal fibroblast cell line. The Fer@AgNP also indicated outstanding compatibility with human RBCs. The results illustrated that biosynthesized Fer@AgNPs have improved antimicrobial efficacy against Gram-negative and Gram-positive pathogenic bacteria with promising biocompatibility and can be used as potential antibacterial agents.